STUDI KELAYAKAN USAHA PENGOLAHAN IKAN SALAI DI DESA TANJUNG MEDAN KECAMATAN TANJUNG MEDAN KABUPATEN ROKAN HILIR - Alrasidi Albi; Hajry Arief Wahyudy (UIR Press, 2023)
The fish processing industry has become a priority program in national development. This sector has proven to be able to survive and be competitive. One that has the potential to be developed is the processing of smoked fish in Tanjung Medan Village. However, the supply of raw materials from fishermen's catches continues to decrease along with the decrease in the amount of fish production due to the deteriorating quality of lake water. This has a significant impact on reducing the number of business actors. Thus, it is necessary to conduct a feasibility study to assess whether this business is profitable and sustainable. This study aims to determine the profile of the business and analyze the feasibility of the financial aspect and the sensitivity of production decline and increase in production costs to business feasibility. The research was conducted in Tanjung Medan Village, Tanjung Medan District, Rokan Hilir Regency. The research method used is a survey method. Data were collected from June to November 2022 and analyzed descriptively using 4 investment criteria. The results show that this business is feasible from a financial perspective. All results of the analysis of investment criteria show a positive value, namely an NPV of IDR 69,000,173; IRR 41.57%; Net B/C Ratio of 2.28; and Payback Period of 3 years 1 month. Meanwhile, the results of the sensitivity analysis show that if there is a 10% reduction in production, it will hurt business feasibility. However, if there is an increase in production costs of 12%, this business is still feasible to run.